Impact of Obstetrician/Gynecologist Hospitalists on Response Time of Obstetric Emergency Operation in Sardjito Hospital Yogyakarta Indonesia: A Retrospective Cohort Study - Eugenius Phyowai Ganap; Mohammad Hakimi; Soerjo Hadijono; Ova Emilia (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2016)
Background: The hospitalist model in obstetric care which was introduced over the last decades now has an important role in care delivery management with the potential positive impact on maternal and neonatal outcomes.Objective: The aim of this study was to evaluate the effect of hospitalist model towards surgical emergency response time.Method: This research design was cohort a retrospective study. Participants included were the patient in the time before and after implementation of obstetrician/gynecologist full-hospitalist policy during October 2013 until September 2014. The outcome measured were mean response time and possible hospital factors which contribute to response time.Result and Discussion: We included a total of 71 patients (30 on-call obstetrician group and 41 full-time hospitalist group). Univariate analysis indicated mean response time was significantly differ in full-time hospitalist group when compared to the on-call obstetrician group (65.3 + 25.89 vs. 84 + 22.29 mins; p = 0.002). Multivariable analysis determined that hospital factors which contribute to response time are readiness of operating theatre.Conclusion: Implementation of full-time hospitalist model is associated with a significant improvement of response time in emergency obstetric care.Keywords: Maternal mortality, Obstetrician/Gynecology Hospitalist, C-section, Response Time